Social isolation in older adults: the role of social exclusion and disconnection - Etchezahar, Edgardo (2025)
Social isolation is considered a common problem in older adults and is defined as the objective lack of social contacts with others along with feelings of exclusion and isolation. 812 cases participated in this study, the average age of the participants was 67.45 years, with an age range between 60 and 80 years. Self-report measures were used through a battery of evaluation instruments composed of: Social isolation, FoMO, Feelings of social exclusion, Social disconnection and sociodemographic data. The results have shown a relationship between FoMO, social exclusion and social disconnection. The scope and limits of the findings are discussed.